AN EXPERIMENTAL INVESTIGATION ON PERFROMANCE ASSESSMENT OF S-ROTORS FOR STAND-ALONE WIND POWER SYSTEM - AHMED BHAYO, BILAWAL (2015)
Generation of electricity for rural remote communities that have low wind potential is nota dream now. It canbepossible with a self-driven, lowspeed, and high torque SRotor. The S-rotors are superior to other wind turbines because they arecheap, require low technicality to manufacture, require low cut-in speed and independent of wind direction. However, these robust design rotors are very low efficient and have negative or almost zero torque angle position, at which theycouldnot self-start. Therefore, the present experimental study isconducted totestseven different S-Rotors inanopen wind flow, to assess their performance and starting characteristics, and to propose suitable design configuration for stand-alone windpowersystem.